CELEBREX IN TREATMENT OF VERTEBRAL PAIN SYNDROME IN SYSTEMICV LUPUS ERYTHEMATOSUS - N. P. Shilkina; N. V. Pizova (Научно-практическая ревматология, 2002)
Celebrex in dosage of 100-200mg/day for 14-20 days was prescribed to 36 SLE pts with symptoms of chronic painful vertebrogenic syndrome. Considerable or moderate lessening of pain syndrome was noticed in 91% of cases (up to 1-3 point by VAS with initial pain more than 4 points). Analgetic effect of the drug was demonstrated already on the 2nd day, the safety was good. Celebrex was recommended for long-term treatment of chronic painful vertebrogenic syndrome in pts with systemic lesions of connective tissue.